Prevalence and correlates of dry nasal snuff use among HIV-infected adult women in South Africa - Jessica L. Elf (Tobacco Induced Diseases, 2018)
Background Dry nasal snuff is a fine powdered smokeless tobacco product inhaled through the nose. People living with HIV (PLWH) in South Africa have a higher prevalence of smoking than their sero-negative peers, however little is known about the prevalence of snuff use or its health effects.